Effects of drop net and helicopter net-gun capture on movement, space use, and survival of white-tailed deer - Dylan G. Stewart; Jared T. Beaver; M. Lucas Cooksey; Chad Grantham; Brian L. Pierce; Roel R. Lopez; Stephen L. Webb (PLoS ONE, 2026)
Wildlife professionals strive to minimize the impact of capture and handling on animal welfare and behavior. Drop net and helicopter net-gun methods are commonly used to capture large mammals; however, comparative evaluations of mortality and post-capture behavioral disruption are needed. Therefore, we conducted a study to compare the effects of drop net, single helicopter, and tandem helicopter capture methods on movement, space use, and survival of white-tailed deer ( Odocoileus virginianus ) for 30 days following capture. We fitted 149 deer (68 F; 81 M) with GPS collars, which collected or were resampled to 1 location every 30 minutes from 2011 to 2015. We estimated daily range size and overlap using 99% range isopleths, calculated daily distance traveled and displacement, and fitted Cox proportional hazards and Kaplan-Meier models to assess survival and estimate survival rates. Survival was similar among capture methods (drop net, S = 0.90; single helicopter, S = 0.94; tandem helicopters, S = 0.94) and was not affected by capture method, capture season, or sex. Deer movement and space use were largely unaffected by capture, with movement returning to long-term means within 1–2 days of capture, but as long as 9 days following helicopter captures. Drop nets had the least effect, likely because capture sites were within or near previously used areas, whereas deer captured by helicopter were transferred 0.5 to 3.1 km. Our findings indicate that these capture methods are effective and have minimal impacts on deer movement, space use, and survival. Helicopter capture methods can be more economical and efficient, but drop nets may pose lower risks to human safety and may be necessary in areas where helicopter access is limited. Our findings provide guidance for wildlife professionals to select capture methods that minimize behavioral modifications while meeting project objectives.